Analysis of patient safety event report categories at one large academic hospital - Mitchell, Cody; Butler, Logan; Holloway, Alexa D.; Ra, Jin H.; Adapa, Karthik; Greenberg, Caprice; Marks, Lawrence B.; Ivester, Thomas; Mazur, Lukasz (Frontiers in Health Services, 2024)
Given the persistent safety incidents in operating rooms (ORs) nationwide (approx. 4,000 preventable harmful surgical errors per year), there is a need to better analyze and understand reported patient safety events. This study describes the results of applying the Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) supported by the Teamwork Evaluation of Non-Technical Skills (TENTS) instrument to analyze patient safety event reports at one large academic medical center. Results suggest that suboptimal behaviors stemming from poor communication, lack of situation monitoring, and inappropriate task prioritization and execution were implicated in most reported events. Our proposed methodology offers an effective way of programmatically sorting and prioritizing patient safety improvement efforts.